Climate as an Evolutionary Driver of Nest Morphology in Birds: A Review - Perez, Daniela M.; Gardner, Janet L.; Medina, Iliana (Frontiers in Ecology and Evolution, 2020)
Avian nests are critical for successful reproduction in birds. Nest microclimate can affect egg development, chick growth and fledgling success, suggesting that nest morphology should be under strong selective pressure to optimize nesting conditions. Given that the internal microclimate of the nest is critical for avian fitness, it is expected that nest morphology is shaped by the local environment. Here we review the relationship between nest morphology and climate across species’ distributions. We collate growing evidence that supports a link between environmental conditions and particular nest traits, within species and across species. We discuss the degree to which phenotypic plasticity in nesting behavior can contribute to observed variation in nest traits, the role of phylogenetic history in determining nest morphology, and which nest traits are likely to be influenced by climatic conditions. Finally, we identify gaps in our understanding of the evolution of nest morphology and suggest topics for future research. Overall, we argue that, although nests are part of the extended phenotype of a bird, they play a crucial role in their reproductive success, and may be an important factor in determining which species will be able to persist in the face of ongoing climate change.